A systematic review of sex-based differences in effectiveness and adverse effects of clozapine - Alberich, Susana; Fernández-Sevillano, Jessica; González-Ortega, Itxaso; Usall, Judith; Sáenz, Marga; González-Fraile, Eduardo; González-Pinto, Ana (Psychiatry Research, 2019)
Clozapine is one of the most widely used antipsychotics for treating psychiatric illnesses such as schizophrenia and bipolar disorder. This drug, however, is associated with adverse effects such as weight gain, metabolic syndrome, and blood dyscrasias. The manifestations of mental illness may differ between men and women. Yet, there is little evidence on the influence of sex on treatment response or the occurrence of AEs. To fill this gap of knowledge, we carried out a systematic review of the literature on sex differences in the effectiveness and adverse effects of clozapine. Scant evidence has been published on differences in effectiveness of clozapine between men and women. Indeed, to the best of our knowledge, this issue has only been addressed in a published study. Regarding adverse effects, males have been reported to be more likely to develop metabolic abnormalities such as cholesterol or triglycerides, hypertension, and cardiovascular risk, while females are at a higher risk for gaining weight, developing diabetes, and needing laxatives. Nevertheless, given the scarcity of sex-based studies on this drug, further studies are needed to explore sex-based differences, as the results obtained may be crucial to clinical practice and help improve the quality of life of patients.
Keywords: clozapine; sex-differences; effectiveness; adverse effects; Scopus; JCR